Neglect and abuse against children and adolescents with nocturnal enuresis: what can be done? - Silvares, Edwiges Ferreira de Mattos (2014)
Risk factors associated to the lack of efficient treatment to enuresis in children and adolescents are evidenced, after short synthesis of the problem etiology and its association to two empirically based treatments (EBT- gold standard). The reasons for treatment omission in old international studies are confirmed on recent ones: a) ignorance about the medical nature of the problem, b) parental negligence and c) offering ineffective homemade strategies. Other risk factors are discussed: parental intolerance associated to treatment attrition and parental violence after enuretic episodes. The confirmation of the abuse by one of two Brazilian studies is discussed in terms of their different sampling and methodology. It is suggested to researchers and health professionals facing this negative scenery a coping attitude: being less reactive or more proactive. Some actions from literature and others from the author’s research team to prevent ignorance, intolerance, negligence and violence close this paper and illustrate the attitude. FAPESP &CNPq.